Roland Barthes' Semiotic Analysis in the Film “Noktah Merah Perkawinan” - Indarsih, Mike; Yuniani, Hani; Astuti, Fajar Diah; Bakiah, Horidatul; Nurpikhasari, Aldinna (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Communication is an activity that is carried out daily, either with people close to us or even with strangers we have just met. Communication seems simple but has various meanings because with communication someone can express their feelings. Assertive communication is the ability to express desires, feelings and thoughts to others while maintaining and respecting the rights and feelings of others. This study aims to interpret the value of assertive communication contained in the film Noktah Merah Perkawinan using Roland Barthes' semiotic approach. The research method used is qualitative descriptive research with a semiotic theory approach. The results of the study using Roland Barthes' semiotic approach can be seen from the connotation, denotation and myth contained in the film Noktah Merah Perkawinan. The results of the interpretation by denotation, connotation and myth show that communication between couples is very much needed. Each partner needs to express their desires, feelings and what is on their minds. The inability to communicate with a partner can cause various problems in the household. The disharmony of a marriage occurs because both parties are unable to communicate well, so that many misunderstandings occur.